NON LITIGATION AS A SETTLEMENT IN THE JUSTICE MODEL OF HANDLING CHILDREN AS VICTIMS : CHILDREN MANAGEMENT STUDY OF MEDAN POLRESTABES) - Surya Nita Surya; Rahul Ardian Fikri Fikri (Jurnal Hukum DE'RECHTSSTAAT, 2023)
Justice of the peace is a peaceful effort or solving criminal cases outside the court used by law enforcement to realize the purpose of law for victims and accused of criminal acts. Justice of the peace is not regulated in the Criminal Procedure Code, but this rule has been regulated in the police, the prosecutor's office and the juvenile criminal justice system. Need to do a first analysis of how the legal basis of Justice of the peace by law enforcement in an effort to provide a sense of justice for victims in the Criminal Procedure Law system in Indonesia?. Second, How does justice of the peace as an effort to provide a sense of justice for victims of child abuse case study in Medan Polrestabes?. The research method is normative juridical by analyzing the rule of law related to restorative justice and case studies of child abuse in Medan Polrestabes. That the regulated Justice of the peace has fulfilled the legal purpose and legal basis of restorative justice in the police with “Perpol No. 8 of 2021 in the settlement of criminal cases in the handling of investigations, the Indonesian prosecutor's regulation in the termination of prosecutions, the Supreme Court issued rules in terms of guidance on using non-litigation settlement from the investigation stage, prosecution to the trial process. That analyze restorative justice case study of child abuse in Medan Polrestabes the peace process is an agreement taken for the benefit of the victim, not the interests of the perpetrator in order to meet the legal objectives of certainty, justice and benefit for the victim.